Pendampingan Pembuatan Aplikasi Penjualan Menggunakan Microsoft Excel Pada UMKM Kripik Tempe Sanan - Ndari, Priska Wulan; Meyana, Yulanda Elis; Lestari, Rini Aprilia (Politeknik Penerbangan Indonesia Curug, 2024)
The increasing use of information and communication technology (ICT) has played an important role in developing Micro, Small and Medium Enterprises (MSMEs) in various sectors. While ICT has great potential to develop MSMEs, there are still challenges such as start-up costs, training, and information security that need to be overcome. However, with the right investment and a good strategy, MSMEs can leverage these technological advantages for growth and success. Sanan Tempe Chips SMEs often have limited resources, including funds, personnel, and technology infrastructure. Purchasing, developing, and maintaining financial applications require significant investment, which these SMEs have not been able to accommodate. This community service activity aims to provide practical solutions for Kripik Tempe Sanan SMEs through assistance in making simple sales applications using Microsoft Excel. Therefore, assistance in making simple sales applications using Microsoft Excel can be a viable alternative for MSMEs with limited resources to improve financial management and business competitiveness. The results of community service activities are able to improve efficiency in recording sales, inventory, and financial reporting of Kripik Tempe Sanan MSMEs. MSME owners and employees feel more confident in using this application after going through training and technical guidance.